PENGARUH WASTE (PEMBOROSAN) DAN VALUE STREAM TERHADAP LEAN SERVICE PERFORMANCE PADA RUMAH SAKIT PRIMA PEKANBARU - Harahap Dahlia Rini; Daulay Nauli Iwan; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The problems that occur in this competitive era, are not only in the manufacturing industry but in the service industry, especially in the industry engaged in the health sector, namely hospitals. This study aims to determine the effect of waste and value stream on employee lean service performance at Prima Pekanbaru Hospital. The sample in this study were employees at Prima Pekanbaru Hospital to 76 respondents. Primary data were collected using a Likert scale questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study was to use multiple linear regression analysis with the help of the SPSS program. The results in this study indicate that: 1) Waste has a significant effect but has a negative relationship to lean service performance at Prima Pekanbaru Hospital, 2) Value stream has a significant and positive effect on lean service performance, 3) Waste and Value Stream has a simultaneous effect on lean service performance on employees at Prima Pekanbaru Hospital.Keywords : Lean Service Performance; Waste; Value Stream; Multiple Linear Regression.